Metaphors of Visibility: Rhetorical Practices in the Normalization of Individual Online Image Management. (October 2020) - Draper, Nora A.
Online image management has become a routine component of contemporary self-presentation. While popular media have concentrated on covering issues related to privacy, individuals in a social environment that prizes visibility face a more implicit mandate to balance concerns about overexposure against the perceived dangers of invisibility. A new class of promotional intermediaries, those that sell personal online reputation management services, have emerged to help individuals navigate the inevitability of "being seen" online with the urgency of image management. These companies apply strategies familiar in advertising and public relations to online self-presentation. This article explores how industry efforts to sell image management as an individual imperative draw on metaphors—including digital tattoo, digital footprint, and digital doppelgänger—to foster anxieties about how our digital identities are constructed, encountered, and interpreted. It argues these metaphors, which warn of the dangers of both visibility and invisibility, reveal a tension that informs popular discourse around digital self-presentation. Ultimately, this article considers how "strategic transparency" is offered to assuage fears, thereby generating a market for personal image management services.